Gender dalam Perspektif Academic Self-Efficacy dan Kecurangan Teknologi Informasi - Hendra Gunawan (JURNAL INTEGRASI, 2012)
This study expands on the research of psychological variables related to link with the cheating information technology (IT). There is very little research that examines the cheating that focuses on IT. Ethical research on students is necessary because IT influences positively on student ethics IT is possible to affect in a positive direction in their IT ethics when they work after graduation. Using the methods of the survey, the research was succeeded in collecting 709 respondents for analysis and tested using the correlation test. The results of this research provide evidence of the relationship between academic self-efficacy with cheating IT.